Diseño de un mecanismo para asignación estratégica de recursos radio en sistemas inalámbricos 5G con Network Slicing - Inga Ilvay, José Luis (2022)
Incorporating Software defined networking and network function virtualization of fifth generation (5G) mobile wireless systems with Network Slicing enables programmable control and efficient management of network resources. In addition, it enables spectral efficiency in the virtual partition of the Radio Access Network (RAN) through resource allocation techniques for a random number of data flows. Considering the real number of bits flowing through a data network connection, these traffic flows can be modeled in different flow classes with predefined transmission profiles, through scheduling fulfilling time-sensitive functions, such as QoS management and load balancing according to required demands. This research work comprises the analysis of the model, mechanism design, simulation and comparison of the data network with resource allocation mechanisms using the balanced fairness technique and maximum-minimum fairness. A Whittle network model was implemented in MatLab software, with the environment's own programming language, using laws, criteria and recursive formulas in a systematic way. This allowed predefining the flow classes with transmission profiles traversing the system with respect to performance metrics; derived from the stationary distribution dependent on the state of the modeled network. Results related to traffic intensity vs. Throughput between different classes with predefined transmission profiles under the stability condition obtained in MatLab, served as a data base for statistical analysis using SPSS software. Validating the designed mechanism, as it is more efficient in flow classes with a greater number of transmission profiles, that is to say, it presents higher performance in flow classes with transmission profiles that generate more of the traffic load.